JURNAL KEBIJAKAN IMIGRASI PRESIDEN BARACK OBAMA DALAM PERBAIKAN KESEJAHTERAAN IMIGRAN ILLEGAL DI AMERIKA SERIKAT. STUDI KASUS : DEFERRED ACTION FOR CHILDHOOD ARRIVALS (DACA) - Andi Hamina (WANUA : Jurnal Hubungan Internasional, 2017)
This study aims to discover the background of President Barack Obama to reform immigration policy in the United States and the impact of immigration policies of President Barack Obama on enhancing illegal immigrants welfare in the United States. The method of research used isdescriptive-analytical. Technique of data collecting is library research. Qualitative analysis is used in analyzing the data, and Deductive as the technique of writing.The results of this study indicate thatthe background of Barack Obama in making immigration policy is to give an opportunities to those seeking a better life, every person who wants to work hard, contribute to the country, and realize their dream to live in freedom. The impact of Presiden Barack Obama Immigration Policy, namely Deferred Action for Childhood Arrivals (DACA) can provide a good influence to improve welfare and protection for illegal immigrants . It is due to an increase in the quality of education, employment opportunities, increase in salary / income, the opportunity to obtain a driving license, a chance to open bank accounts and credit cards, more confident in socializing with the community, and protection from deportation for two years.